Correction: Biocompatible graphene oxide as a folate receptor-targeting drug delivery system for the controlled release of anti-cancer drugs. Issue 22 (11th March 2015) - Zhao, Xubo; Liu, Peng
<x xml:space="preserve">Abstract</x> Correction for 'Biocompatible graphene oxide as a folate receptor-targeting drug delivery system for the controlled release of anti-cancer drugs' by Xubo Zhao et al., RSC Adv., 2014, 4, 24232–24239.